Kidney Transplantation Rates Across Glomerulonephritis Subtypes in the United States. Issue 10 (October 2017) - O'Shaughnessy, Michelle M.; Liu, Sai; Montez-Rath, Maria E.; Lafayette, Richard A.; Winkelmayer, Wolfgang C.
Abstract : Background: Whether kidney transplantation rates differ by glomerulonephritis (GN) subtype remains largely unknown. Methods: Using the US Renal Data System, we identified all adult patients with end-stage renal disease attributed to 1 of 6 GN subtypes who initiated dialysis in the US (1996-2013). Patients with diabetic nephropathy (DN) and autosomal-dominant polycystic kidney disease (ADPKD) served as "external" non-GN comparators. Using Cox proportional hazards regression, with death considered a competing risk, we estimated hazard ratios (HRs) (95% confidence intervals [CI]) for first kidney transplantation, controlling for year, demographics, comorbidities, socioeconomic factors, and Organ Procurement Organization. Results: Among 718 480 patients studied, unadjusted and multivariable-adjusted transplant rates differed considerably across GN subtypes. Adjusted transplant rates were highest for patients with IgA nephropathy (IgAN) (referent) and lower for all other groups: focal segmental glomerulosclerosis (HR, 0.80; 95% CI, 0.77-0.82), membranous nephropathy (HR, 0.88; 95% CI, 0.83-0.93), membranoproliferative GN (HR, 0.84; 95% CI, 0.76-0.92), lupus nephritis (HR, 0.69; 95% CI, 0.66-0.71), vasculitis (HR, 0.66; 95% CI, 0.61-0.70), DN (HR, 0.50; 95% CI, 0.47-0.52), ADPKD (HR, 0.85; 95% CI, 0.82-0.88). Reduced kidney transplantation rates among comparator groups were driven more so by lower rates of waitlisting (HRs vs IgAN, ranged from 0.49 for DN to 0.92 for membranous nephropathy or ADPKD) than by lower rates of deceased donor kidney transplantation after waitlisting (rates were only significantly lower, vs IgAN, for those with secondary GN subtypes: lupus nephritis [HR, 0.91; 95% CI, 0.86-0.97], vasculitis [HR, 0.85; 95% CI, 0.76-0.94), DN [HR, 0.73; 95% CI, 0.69-0.77]). Conclusions: Identifying underlying reasons for apparent disease-specific barriers to kidney transplantation might inform center-specific transplant candidate selection procedures, along with national organ allocation policies, leading to more equitable patient care and improved patient outcomes. Abstract : Using the US Renal Data System, the authors report on a lower adjusted transplant rate in patients with a primary glomerulonephritis (except for IgA nephropathy) when compared to patients with diabetic nephropathy or autosomal-dominant polycystic kidney disease. The main cause is reduced listing of these patients. Supplemental digital content is available in the text.